Comparative Analysis of Government Regulatory Compliance: A Case of Kenya, China and USA (International Journal of Scientific Research and Management (IJSRM), 2024)
The importance of regulatory compliance in ensuring that laws and related public policies accomplish their intended goals, which include promoting social and economic development and protecting important aspects of public welfare in a nation cannot be gainsaid. Championing regulatory compliance is a crucial part of international development work, as much as it is frequently overlooked. Studies reveal that the "volume" and harshness of enforcement do not always correspond with compliance and regulatory outcomes, that compliance is not always the intended result of regulations, and that compliance is not always the automatic consequence of regulations. Robust data also indicates that regulations, regulatory administration, procedures, and systems that are not well-designed can impede economic expansion and serve as a breeding ground for corruption. This study digs into the complexities of government regulation compliance in the ever-evolving field of e-commerce, providing a comparative examination among three very different jurisdictions: Kenya, the United States and China. The purpose of the study is to clarify the constantly changing regulatory environment that oversees Internet commerce by investigating the legal frameworks, enforcement strategies, and commercial ramifications that arise for companies that operate in these various areas. The research endeavors to enable cross-border cooperation and enlighten policymakers on effective regulatory strategies to balance innovation, consumer protection, and industrial growth by identifying commonalities and discrepancies in regulatory approaches. This research offers a contemporary overview of the legislative frameworks driving the digital marketplace in various regions, as e-commerce continues to redefine global trade dynamics.